Evaluating critical factors of Chinese calligraphy's psychological effects on Chinese college students - Liu, Ying; Perumal, Velu; Suppiah, Subapriya; Poh, Foong Lee; Wu, Yue (Green Publication, 2024)
The large magnitude of changes in the world's socio-economic, political, and technological landscape and the prevalence of COVID-19, have resulted in Chinese college students experiencing increased psychological problems. The usage of art has traditionally been linked with the alleviation of psychological problems such as depression and anxiety. Hence, there is a need to evaluate the critical factors of Chinese calligraphy handwriting (CCH) and use it to improve the overall health and academic success among college students. Thisstudy reviews the literature to identify the methods for enhancing psychological problems among Chinese college students, CCH characteristics, and its effectiveness in mental health intervention. We aim to evaluate the critical factors of CCH in improvingthe psychological problems among Chinese college students using objective assessments. In our review, we include therapeutic approaches to psychological issues among Chinese college students, the CCH fonts, characters, patterns, and content, and the CCH as an intervention on the body and the mind, listing the therapeutic applications and effects of calligraphy. CCH is proposed as a comprehensive solution to Chinese college students' psychological problems, thereby improving academic success and overall well-being.